Treatment of benign bone tumors: judicious use of adjuvants result in better functional outcomes - Hemant More; Zile S Kundu; Roop Singh; Mohit Khanna; Jitendra Wadhwani; Pradeep Kamboj (International Journal of Medical Research and Review, 2022)
Background: While curettage has been a common treatment option for low grade benign lytic bone lesions, a careful extension of curettage enhances it’s efficacy without compromising the integrity of surrounding normal bone. Many adjuvants are used for extension of curettage, but all are not universally available, and each has it’s own drawbacks. We report outcome of extended curettage of benign lytic bone lesions using high-speed burr, electrocautery, hydrogen-peroxide, and pulsatile lavage. Methods: The study was conducted on 25 patients,10 to 40 years in age, with lytic bone lesions proven benign. Tumors belonged to Campanacci Grade 1 and 2 of varying histological types. High-speed burr, electrocautery, hydrogen-peroxide, and pulsatile lavgage were extensively used after curetting the lesions with sharp curettes. Defects were filled with bone graft or substitute where needed, if the cavity size was more than 1/3rd of the width of the bone on radiographic assessment. Patients were reviewed for minimum 18months. Results: All defects reverted to near-normal radiological appearance with excellent functional outcome recorded in most cases. Eighty percent patients recovered uneventfully. Mild limited complications were noted as prolonged period of pain in 12% and superficial infection in 8%. No local recurrence was observed. Conclusions: This study demonstrates the efficacy of extended curettage in treatment of benign tumors and tumor like lesions of bone using simple cheap modalities which are universally available. In properly selected cases of benign bone tumors, a meticulously performed extended curettage provides an effective treatment option that safeguards functionality without compromising on safety.